2016
DOI: 10.1159/000445615
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CPU0213, a Dual Endothelin Receptor Antagonist, on Apoptosis via Nox4-Dependent ROS in HK-2 Cells

Abstract: Background/Aims: Our previous studies have indicated that a novel endothelin receptor antagonist CPU0213 effectively normalized renal function in diabetic nephropathy. However, the molecular mechanisms mediating the nephroprotective role of CPU0213 remain unknown. Methods and Results: In the present study, we first detected the role of CPU0213 on apoptosis in human renal tubular epithelial cell (HK-2). It was shown that high glucose significantly increased the protein expression of Bax and decreased Bcl-2 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…With increasing age, the disease progressed and kidney function deteriorated further, resulting in a significant rise in albuminuria and renal fibrosis. Though there were some studies about the roles of some potential chemicals or drugs on diabetic kidney injury, our study showed the new role and mechanism of VDR agonist [22, 23]. The results from the present study demonstrated that paricalcitol possessed an impressive renal protective efficacy in DN.…”
Section: Discussionmentioning
confidence: 48%
“…With increasing age, the disease progressed and kidney function deteriorated further, resulting in a significant rise in albuminuria and renal fibrosis. Though there were some studies about the roles of some potential chemicals or drugs on diabetic kidney injury, our study showed the new role and mechanism of VDR agonist [22, 23]. The results from the present study demonstrated that paricalcitol possessed an impressive renal protective efficacy in DN.…”
Section: Discussionmentioning
confidence: 48%
“…Cytokine is one of the major mediators composing the immune system, and change of immunological function is one of the leading causes of DN occurrence [29, 30]. TNF-α is essential in the regulation of inflammation in the kidney, and is correlated with renal injury and a disruption of the glomerular permeability barrier in patients with diabetes [15, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory factors such as ET A , IL6 and TNFα are also linked with oxidative stress and inflammation, and they are involved in the pathological process of many diseases, including nephropathy and cardiovascular complications. 22,23 Endothelin is related to AQP4 and the water balance within cells. ET-1 overexpression in the brain caused cerebral edema in astrocytes, which expressed AQP4.…”
Section: Discussionmentioning
confidence: 99%